Doping-induced electronic modulation of electrocatalysts for CO2 reduction reaction - Chen, Mengxin (Nanyang Technological University, 2024)
The heavy reliance on fossil fuels and the subsequent increase in CO2 emissions have contributed to anthropogenic climate change. To mitigate the rise in atmospheric CO2 concentration, various approaches including biological, thermos-catalytic, and (photo) electrochemical methods have been explored for CO2 reduction to chemicals and fuels. Among these methods, electrochemical CO2 reduction reaction (CO2RR) powered by sustainable energy offers a promising solution. However, the current catalysts employed for CO2RR do not meet the required activity and selectivity standards for specific carbonaceous products in industrial applications. Recently, many studies have emphasized the potential of non-noble metal-based materials as efficient catalysts for converting CO2 into desired products, considering factors like cost, abundance, and environmental impact. However, the limited selectivity and activity of these electrocatalysts present challenges for their widespread industrial application. Therefore, this dissertation focuses on the electronic modulation of electrocatalysts through various types of doping, especially non-noble metal-based material, for improving the performance of the CO2 reduction reaction. The mechanisms underlying these strategies have been thoroughly analyzed to assist the systematic development of high-efficiency catalysts. In the first work, electronic structure of Sn-based catalysts is modulated through anion doping. The synthesis of SnS2 nanoflowers is achieved using hydrothermal methods. Experimental results demonstrate that the as-prepared SnS2 undergoes in situ dynamic restructuring during reaction process, leading to the creation of nanoflowers composed S-doped Sn metal nanosheet, which is the active sites for catalyzing CO2 to formate. Both experimental and theoretical findings reveal that S-doping induces a higher oxidized valence state of the active site Sn, facilitating the activation of CO2 and fast charge transfer at the interface of electrode and electrolyte and. The theoretical analysis further shows that S-doping optimizes the adsorption energy of the *OCHO onto the active Sn site while suppressing the CO2RR to CO pathway, leading to significantly enhanced formate selectivity in a wide operating window. The S-doped Sn catalyst display as a selectivity more than 50% to formate with a range of -0.7 to -1.3 V vs. RHE. In the second part, the combination of cation doping and structure engineering is employed in Sn-based materials to further optimize the electronic structure of active Sn sites, as S dopants alone in Sn sites are insufficient to suppress the H2 generation. Copper dopants are incorporated into the SnS2 matrix without generating new phases. Experimental findings reveal that the Cu-doped SnS2 nanoflower goes for dynamic restructuring in CO2RR process, leading to forming the active S-doped Cu/Sn alloy. Theoretical and experimental observations show the modification of the electronic structure through the combination of S-doping together with Cu-alloying enables the finely tuned the adsorption strength of the intermediate HOCO* onto the active Sn site, leading to exceptional selectivity towards formate. Remarkable Faradaic efficiencies exceeding 80% are achieved over a wide operating window of -0.8 to -1.3 V vs. RHE. Notably, the greatest selectivity of ~90.5% is attained at -1.0 V vs. RHE, realizing a current intensity of -23.8 mA cm-2 for formate. In addition, the catalyst demonstrates exceptional long-term stability, maintaining Faradaic efficiency of 80% towards formate over a continuous period for more than 120 hours at around -16.5 mA cm-2. In the third part of this research work, drawing upon the comprehension of how different types of dopants interact to engineer the electronic configuration of electrocatalysts, the successful incorporation of different metal dopants into N-doped graphitic carbon through in situ high-temperature pyrolysis results in the formation of Metal-Nx bonds with pyridinic-N, which plays the role of the active site for catalyzing CO2 conversion. The interaction between Cu-Nx and Mn-Nx sites is found to increase charge transfer and engineer the electronic structure of Cu-Nx and Mn-Nx sites, resulting in significantly enhanced selectivity towards CO2RR products (> 75%) during a wide operating window of -0.47 to -1.07 V vs. RHE. Notably, the CuMn-N-C catalyst displays a steady current intensity of roughly -7.5 mA cm-2 with sustaining high selectivity over 80% for CO2RR products for an extended period of 35 hours.